Imaging transporters: Transforming diagnostic and therapeutic development. Issue 5 (18th August 2016) - Mann, A; Han, H; Eyal, S
Abstract : Molecular imaging allows noninvasive assessment of drug distribution across pharmacological barriers. Thus, it plays an increasingly important role in efforts to understand the interactions of molecules with membrane transporters during drug development and in clinical pharmacology. We describe established and emerging imaging modalities utilized for studying transporter expression and function. We further present examples of how molecular imaging could provide insights into the contribution of transporters to drug disposition and effects.